How intellectual capital drives firm value: Corporate governance as an antecedent in Jakarta Islamic Index - Rosita, Rosita; Susanto, Heri; Fuady, Misbach (Journal of Accounting and Investment, 2026)
Research aims: This study investigates the interplay among Corporate Governance (CG), Intellectual Capital (IC), and firm value for companies indexed in the Jakarta Islamic Index (JII), specifically analyzing how IC acts as a mediating link connecting governance practices to market valuation. Design/Methodology/Approach: Employing a quantitative methodology, the study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze Sharia-compliant enterprises over an extended observation period, measuring CG indicators, IC via Value-Added Intellectual Coefficient (VAIC), and company value using Tobin's Q. Research findings: Results indicate that CG and IC are positively correlated, whereas firm value exhibits mixed outcomes. Crucially, intellectual capital successfully mediates the relationship between CG and firm value, demonstrating that effective governance optimizes firm value primarily by enhancing intellectual capital. Theoretical contribution/Originality: This study extends resource-based view (RBV) and agency theories within an Islamic capital market context, offering empirical evidence on how structural governance mechanisms translate into intangible asset optimization (intellectual capital) to drive market value in Sharia-compliant firms. Practitioner/Policy implication: Corporate managers and policymakers of Islamic enterprises should prioritize strategic investments in human, structural, and relational capital, aligning corporate governance frameworks to actively cultivate intellectual capital as a core driver of sustainable firm valuation. Research limitation/Implication: The study's scope is restricted to companies listed on the Jakarta Islamic Index (JII), which may limit the generalizability of findings to conventional markets or other international Islamic indices; future research could incorporate broader market comparisons and dynamic longitudinal variables.